2020
DOI: 10.1038/s41438-020-0320-6
|View full text |Cite
|
Sign up to set email alerts
|

Apple SERRATE negatively mediates drought resistance by regulating MdMYB88 and MdMYB124 and microRNA biogenesis

Abstract: The function of serrate (SE) in miRNA biogenesis in Arabidopsis is well elucidated, whereas its role in plant drought resistance is largely unknown. In this study, we report that MdSE acts as a negative regulator of apple (Malus × domestica) drought resistance by regulating the expression levels of MdMYB88 and MdMYB124 and miRNAs, including mdm-miR156, mdm-miR166, mdm-miR172, mdm-miR319, and mdm-miR399. MdSE interacts with MdMYB88 and MdMYB124, two positive regulators of apple drought resistance. MdSE decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…We speculate that their upregulation may have contributed to the increased drought tolerance of MdSIZ1 RNAi plants. In addition, previous studies have found that the dwarf phenotype may be related to plant miRNA level [6,64] . Our stemloop qRT-PCR analysis demonstrates that the drought positive regulators mdm-miR168 and mdm-miR72 were upregulated in transgenic lines under normal and drought conditions [44,45] .…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…We speculate that their upregulation may have contributed to the increased drought tolerance of MdSIZ1 RNAi plants. In addition, previous studies have found that the dwarf phenotype may be related to plant miRNA level [6,64] . Our stemloop qRT-PCR analysis demonstrates that the drought positive regulators mdm-miR168 and mdm-miR72 were upregulated in transgenic lines under normal and drought conditions [44,45] .…”
Section: Discussionmentioning
confidence: 96%
“…RNAi plants under drought stress. The positive regulators of drought stress, MdDREB2A, MdPIP1;3 and MdNCED3 [6,41,43] , were induced to a greater extent in MdSIZ1 RNAi transgenic plants than in GL-3 ( Fig. 9).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In fruit trees, water deficit inhibits flower bud differentiation and tree vegetative growth, thereby causing flowers and fruits to drop (Virlet et al, 2015; Niu et al, 2019). To cope with drought stress, plants respond at both the morphological and molecular levels, exhibiting changes in photosynthesis, stomatal movement, hormone content, leaf development, stem extension, root proliferation, hydraulic conductivity, and gene expression (Yordanov et al, 2000; Seiler et al, 2011; Basu et al, 2016; Liao et al, 2016; Sun et al, 2018; Geng et al, 2020; Li et al, 2020). Therefore, decoding the molecular mechanisms that underlie drought responses is critical to the development of new cultivars for future agriculture (Sun et al, 2013b; Liao et al, 2016; Geng et al, 2018; Sun et al, 2018; Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%